(3QSGdI YHO GdYRjR Hf eGfYs - (3YHO GdYRjR Hf eMeO Hf eGfYs; (3GHf HGOjSs
(3ChdgG (B:s
(3ef YHO GdYRjR Hf eMeO Hf eGfY Edi GdTjN YHO Gddg Hf eMeO Hf ONjd hHYO abO HdZfG JTfjYc Ydi CNjc hgPG CNj djS ef GdOjg hdG ef SfI YHGO Gddg GdUGdMjf s
(3BNQgG (B:s
(3hEPG cGf bejU Ch LHI aEfgG LGFRI CNj cdGefG ai GdeYGfbI eG HdZ gPG GdMO hUdi Gddg Ydi eMeO hBdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs